Karakteristik Dinding Batu Bata Menggunakan Campuran Sedimen dan Tanah Liat - Fadlun Pratama Y. Mangge; Frice Lahmudin Desei; Yuliyanti Kadir (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Bricks are artificial stones made from clay, with or without additional materials, dried and fired at high temperatures to achieve durability. This study aims to analyze the characteristics of sediment from the dredging of Lake Limboto, determine the optimal mixture composition of sediment and clay for brick production, assess the compressive strength of bricks using this mixture, and outline the brick-making process. The research utilizes primary data collected through field surveys, interviews, and observations in Ilohungayo Village, Batudaa District, Gorontalo Regency. After molding and drying, compressive strength tests were conducted on different sample compositions. The results indicate that sediment-based bricks have lower water content than clay-based ones. In Sample I, the highest water content (77.9%) was observed in a 50% sediment and 50% clay mixture, while the lowest (35.9%) was in 100% clay. In Sample II, the highest water content (79.1%) was in 100% clay, while the lowest (34.1%) was in a 70% sediment and 30% clay mixture. Compressive strength tests revealed that all samples fell below the SNI 15-2094-2000 standard for red bricks but met the SNI 03-0349-1989 standard for concrete bricks, classified as class III and IV solid bricks. The study concludes that incorporating Limboto Lake sediment into brick production enhances cost-effectiveness and sustainability by reducing sediment accumulation in the lake while producing stable and economical bricks.